2011
DOI: 10.1682/jrrd.2010.06.0117
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment as barrier to engagement in vocational services among veterans with severe mental illness

Abstract: Abstract-Vocational services (VS), particularly supported employment models, have clear advantages for assisting adults with severe mental illness (SMI) in returning to the workplace, but a majority of eligible individuals with SMI do not receive any type of VS. The reasons for nonparticipation in VS remain poorly understood, and the potential contribution of cognitive impairment as a barrier to entry has not been explored. The present study uses a pathways-to-care design to examine the specific contribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 73 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…Interactions between TBI sequelae and psychological health conditions may contribute to a downward spiral affecting occupational functioning [18]. OIF/OEF Veterans with multiple mental health conditions, but particularly those who also have a history of TBI and associated cognitive impairments, may face more barriers to workforce participation and may be among those most likely to seek VHA vocational services [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between TBI sequelae and psychological health conditions may contribute to a downward spiral affecting occupational functioning [18]. OIF/OEF Veterans with multiple mental health conditions, but particularly those who also have a history of TBI and associated cognitive impairments, may face more barriers to workforce participation and may be among those most likely to seek VHA vocational services [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, PTSD may be an impediment to employment, even in programs emphasizing work readiness rather than competitive employment such as TWE; Resnick and Rosenheck found that Veterans with PTSD were 19 percent less likely to be employed at discharge from the program than Veterans without PTSD and concluded that supported employment, which is primarily targeted to individuals with severe mental illness, may need to be modified to meet the needs of Veterans with PTSD [14]. Cognitive impairment, common among individuals with mental health conditions, appears to make navigating the pathways to vocational services offered by VHA difficult [15]. Veterans with a psychiatric disorder and sequelae of TBI, typically seen in VHA polytrauma clinics, may be most likely to experience cognitive barriers to entering vocational services.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in bipolar disorder, cognitive deficits have been shown to be associated with reduced psychosocial function [11,12]. Cognitive impairment is an important determinant of poor engagement with vocational rehabilitation services [13] and failure to maintain job tenure [14]. Research into measures to improve cognition is therefore driven by the hope that such improvements might lead to better long-term economic as well as functional outcomes, along with greater opportunities for social inclusion.…”
Section: Cognitive Impairment In Severe Mental Illnessmentioning
confidence: 99%
“…[20]. It is notable that 7 Veterans (10%) were not interested in employment or vocational services, which may suggest that even if services were offered, there would be a significant minority who would not participate because of lack of interest in employment.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a sample of more than 4,000 Army Veterans with a psychiatric diagnosis, such as depression, generalized anxiety disorder, or posttraumatic stress disorder (PTSD) and no history of mTBI, the incidence of postconcussive syndrome symptoms, including cognitive difficulties, was greater than it was for Veterans with a history of mTBI [19]. Veterans with cognitive impairment are at significantly greater risk for poor employment outcomes [10], and moderate cognitive impairment has been associated with poor engagement in vocational rehabilitation in a Veteran sample [20].…”
Section: Introductionmentioning
confidence: 99%